2021
DOI: 10.3389/fmed.2021.634177
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in Monocyte Function in Age Related Macular Degeneration: A Novel Systemic Change Associated With the Disease

Abstract: Age-related macular degeneration (AMD) is characterized by the accumulation of debris in the posterior eye. In this study we evaluated peripheral blood monocyte phagocytic function at various stages of AMD and in aged matched control participants. Real-time tri-color flow cytometry was used to quantify phagocytic function of peripheral blood monocyte subsets (non-classic, intermediate and classic) isolated from subjects with intermediate or late AMD and compared with age matched healthy controls. Assessment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 54 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…The phenotypic heterogeneity of monocytes after GA immunization appeared to provide protection against drusen formation and reduced established total drusen area. Additionally, GA-mediated Th2 cells were shown to reduce retinal microglial cytotoxicity, likely induced by amyloid [24]. Another AMD study found a decrease in macular plaque formation [93].…”
Section: Therapeutic Roles Of Ga In Ophthalmic Disordersmentioning
confidence: 97%
See 4 more Smart Citations
“…The phenotypic heterogeneity of monocytes after GA immunization appeared to provide protection against drusen formation and reduced established total drusen area. Additionally, GA-mediated Th2 cells were shown to reduce retinal microglial cytotoxicity, likely induced by amyloid [24]. Another AMD study found a decrease in macular plaque formation [93].…”
Section: Therapeutic Roles Of Ga In Ophthalmic Disordersmentioning
confidence: 97%
“…Overall, GA promotes and improves phagocytic activity of monocytes and microglia towards myelin debris [13,22,23]. Thus, GA has been shown to impact the phenotype of myeloid cells, including monocytes and microglia, within the periphery and cerebral microenvironment [18,22,24,25].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 3 more Smart Citations